2005
DOI: 10.1557/jmr.2005.0101
|View full text |Cite
|
Sign up to set email alerts
|

Early interaction between Fe–Cr alloy metallic interconnect and Sr-doped LaMnO3 cathodes of solid oxide fuel cells

Abstract: The initial stages of the interaction between the Fe-Cr alloy metallic interconnect and Sr-doped LaMnO 3 (LSM) electrode of solid oxide fuel cells (SOFC) were investigated under cathodic polarization at the temperature range of 700-900°C. Cr deposits on the Y 2 O 3 -ZrO 2 (YSZ) electrolyte surface increased with the polarization time. However, it was observed that at the early stages of the reaction, there is no preferential Cr deposition at the three-phase boundary areas at the LSM electrode/YSZ electrolyte i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
108
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(117 citation statements)
references
References 32 publications
8
108
1
Order By: Relevance
“…This preferential Cr 2 O 3 deposition at the three-phase boundary (electrolyte-electrode-gas), where the chromium-containing gas, oxygen vacancies and electron holes are available, as shown schematically in Fig. 2, supports the electrochemical mechanism [18,20,23,26,27,31,32,36]. The deposition reaction shown in Fig.…”
Section: Chromium Poisoningsupporting
confidence: 63%
See 2 more Smart Citations
“…This preferential Cr 2 O 3 deposition at the three-phase boundary (electrolyte-electrode-gas), where the chromium-containing gas, oxygen vacancies and electron holes are available, as shown schematically in Fig. 2, supports the electrochemical mechanism [18,20,23,26,27,31,32,36]. The deposition reaction shown in Fig.…”
Section: Chromium Poisoningsupporting
confidence: 63%
“…Although such an increase in the amount of degradation with increasing temperature has been observed [31], this is not always the case. For example, Kaun et al [30] and Kim et al [39] reported that the amount of degradation increased as the temperature was decreased from 800 to 700 • C and 850 to 750 • C, respectively.…”
Section: Chromium Poisoningmentioning
confidence: 89%
See 1 more Smart Citation
“…However, it has been widely observed that volatilized chromium vapor species readily react with LSM to form both (Mn,Cr) 3 O 4 and (La,Sr)(Cr,Mn)O 3 in SOFC environments [28][29][30]. The work by Jiang et al [31] demonstrated that Cr deposition at the LSM/YSZ interface was primarily due to the generation of Mn 2+ ions during cathodic polarization, which readily reacted with the CrO 3 vapor species to form (Mn,Cr) 3 O 4 on the YSZ surface. This not only confirmed the reactivity of LSM with Cr vapor species but also indicated that the Mn-Cr spinel was not captured by or attached to the LSM surface; rather, the spinel deposited preferentially on the yttria-stabilized zirconia (YSZ).…”
Section: Comparison Of Cr Migration For Different Composite Contact Mmentioning
confidence: 99%
“…However, rapid oxidation kinetics, easy spalling tendency of the oxide scale and the formation of chromia as an oxide (which has a high electrical resistivity and a high volatility as hexavalent Cr [5][6][7]) restrict the use of many of the commercially available iron-based and nickel-based alloys as SOFC interconnect to short term applications. Currently, FeCr alloys are being explored for application as SOFC interconnect [8][9][10][11][12]. The Fe-Cr alloys, typically ferritic stainless steels, are generally better matched in thermal expansion coefficient (around 11-13 x 10 -6 K -1 ) with that of other cell components than Ni-Cr alloys, and are relatively inexpensive.…”
Section: Introductionmentioning
confidence: 99%